Steamers NORTH PACIFIC and LYDIA THOMPSON at the Chautauqua dock, Ellisport, Vashon Island, Washington, 1893 - University of Washington Libraries. Special Collections Division. (1893)
Caption on mount: At Chautaqua Vashon dock, 1893, Strs. No. Pacific & Lydia Thompson. The North Pacific Co. operated the old Puget Sound side-wheel steamer NORTH PACIFIC to Skagway and Dyea early in the 1898 season, departing Seattle every 15 days carrying 150 first-class and 150 second-class passengers and 70 tons of freight. She made her last voyage from the north on April 26, 1898, and was then temporarily laid up at Port Townsend before resuming local service on Puget Sound. (pg. 36) The steamer LYDIA THOMPSON was in passenger and freight service in Puget Sound and Alaska waters for 53 years and sank in early October 1946 in Lake Union. (pg. 536) Notes from Gordon Newell, ed., The H.W. McCurdy Marine History of the Pacific Northwest (Seattle: Superior Publishing Co, 1966). To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number